Risk of serious bacterial infections in inflammatory rheumatic or bowel disease patients during biological therapies: nationwide Danish cohort study - Emma Cathrine Højberg Platz; Gustav Emil Laugesen; Anne Ahrens Østergaard; Keld-Erik Byg; Inge Petersen; Isik Somuncu Johansen (Annals of Medicine, 2025)
Introduction To estimate the incidence rate ratio (IRR) of serious bacterial infections (SI) in patients with inflammatory bowel disease (IBD) or inflammatory rheumatic disease (IRD) before and after initiating biological therapy, and to assess comorbidities, infection sites, and the type of biological therapy.Methods This nationwide retrospective registry-based study used a cohort-crossover design to assess the relative risk of SI one year before and after treatment. Data from the Danish National Patient Registry included 20,216 patients with IBD or IRD. Diagnosis codes for hospital contacts (inpatients, outpatients, day patients, and emergency department patients) and hospital-treated bacterial infections from 1994 to 2018 were linked using the Civil Registration System.Results There were 1235 infections during 19,529 person-years one year before treatment, compared to 1251 infections over 17,831 person-years one year after treatment initiation (IRR = 1.11, 95% CI [1.03–1.19], p = 0.01). The incidence rate was 2-fold higher in the first three months post-treatment compared to over one year. Increased risks were found for bacterial infections without specified site; ear, nose, and throat; and respiratory tract infections. Higher risks of SI after treatment initiation were associated with comorbidities, treatment initiation between 2015 and 2018, age ≥61 at inflammatory disease diagnosis [HR = 1.50 (1.31–1.72)], female sex, and corticosteroid co-administration. Anakinra showed a significantly increased risk of infection [HR = 2.02, 95%CI 1.03–3.97)] in IRD patients.Conclusions We found a modestly increased risk of SI in the year following therapy initiation, with the highest risk in the first three months. This risk was associated with certain baseline factors, highlighting the need for thorough risk assessment when starting treatment.